ChemInform Abstract: Corrin Syntheses. Part 6. Corrin Synthesis via (A→D) Ring Closure. The Construction of A/D‐Secocorrin Chromophore Systems by the "Sulfide Contraction" Method and the Photochemical A/B‐Secocorrin→Corrin Cycloisomerization. Issue 8 (February 2016) - Eschenmoser, Albert; et al.
Abstract: Review: [104 refs.